Characterization of Antibacterial Compounds from Marine Sponge-associated Streptomyces spp. against Some Pathogenic Bacteria - Efendi, Firda Sri; Budiarti, Sri; Lestari, Yulin (HAYATI Journal of Biosciences, 2025)
The increasing trend of antibiotic resistance among pathogenic bacteria is a worldwide problem. Streptomyces produce a number of bioactive compounds such as antibacterial. This study aimed to investigate the effect of different media and incubation time in increasing the antibacterial activity of marine sponge-associated Streptomyces spp. and characterize antibacterial compounds of marine sponge-associated Streptomyces spp. against pathogenic bacteria. Among the three tested media and some days of incubation times, Streptomyces spp. produce more antibacterial activity when grown using modified molasses medium at 15 days incubation. The ethyl acetate extracts of Dbi28t exhibited a significant inhibitory zone against Extended Spectrum β-Lactamase (ESBL)-producing Escherichia coli, Providencia rettgeri then followed by Proteus mirabilis and Pseudomonas putida and the results were higher than some commercial antibiotics. This study has identified nine antibacterial compounds in Dbi28t using Liquid Chromatography-tandem Mass Spectrometric (LC-MS/MS) analysis, with the most abundance belonging to pumilacidin A, then followed by pumilacidin B, surfactin B, surfactin A, phenazostatin B, chalcomycin B, neopyrrolomycin C, saquayamycin A and saphenamycin. This work provides the first report from a Streptomyces sp. Dbi28t produced pumilacidin, surfactin and other bioactive compounds with the modified molasses medium for optimization of characterization of its antibacterial compounds.